Hydrogelation tunability of bioinspired short peptides. Issue 44 (27th October 2022) - La Manna, Sara; Florio, Daniele; Panzetta, Valeria; Roviello, Valentina; Netti, Paolo Antonio; Di Natale, Concetta; Marasco, Daniela
Abstract : The fragment 269–273 of nucleophosmin 1 protein, was investigated in its ability to form hydrogels in four different forms deriving from the partial, absent and complete amidation/acetylation at the extremities of the backbone. Abstract : Supramolecular assemblies of short peptides are experiencing a stimulating flowering. Herein, we report a novel class of bioinspired pentapeptides, not bearing Phe, that form hydrogels with fibrillar structures. The inherent sequence comes from the fragment 269–273 of nucleophosmin 1 protein, that is normally involved in liquid–liquid phase separation processes into the nucleolus. By means of rheology, spectroscopy, and scanning microscopy the crucial roles of the extremities in the modulation of the mechanical properties of hydrogels were elucidated. Three of four peptide showed a typical shear-thinning profile and a self-assembly into hierarchical nanostructures fibers and two of them resulted biocompatible in MCF7 cells. The presence of an amide group at C-terminal extremity caused the fastest aggregation and the major content of structured intermediates during gelling process. The tunable mechanical and structural features of this class of hydrogels render derived supramolecular systems versatile and suitable for future biomedical applications.